Thermal conductivity of different bio-based insulation materials - Sergej Medved; Eugenia Mariana Tudor; Marius Catalin Barbu; Timothy M. Young (Les)
To achieve the zero-waste goal as well as sustainability, the use of the raw materials, especially those from nature, and wood in particular, has to be smart, meaning that the resource has to be used to its full potential. Since wood-based industry is associated with high intensity and the generation of a relatively large amount of residues, those residues should be used for the production of useful products, otherwise they will easily be classified as waste and afterwards used as a source of energy. To present a possible solution for wood residues like wood chips, wood particles and bark, we investigated the possibility of using wood and bark residues as constituents for the production of single layer insulation panel with a target thickness of 40 mm and target density of 0.2 g·cm-3. Thermal conductivity was determined using the steady state principle at three different temperature settings. The average thermal conductivities were determined between 49 mW·m-1·K-1 and 74 mW·m-1·K-1. The highest values were determined at boards made from bark, which also had the highest density (0,291 g·cm-3), while the lowest thermal conductivity was observed for boards made from spruce wood particles.